Is it necessary to repeat cervical cytology at the tie of a colposcopy? É necessário repetir a citologia cervical no momento da colposcopia? - Leticia Maria Correia Katz; Alex Sandro Rolland Souza; Juliana Melo de Moraes Guerra; Melania Maria Ramos Amorim (Instituto Materno Infantil de Pernambuco, 2012)
OBJECTIVES: to evaluate whether repeating Papanicolaou smear testing at the time of colposcopy improves agreement between cytology and histopathology in the diagnosis of cervical cancer. METHODS: this cross-sectional study included 397 women referred for colposcopic evaluation following an abnormal cervical smear test. The cytology was repeated at the time of the colposcopy using a conventional medium. The two cytology tests were compared with each other and with the histopathological findings obtained by colposcopy-directed biopsy. The 2001 Bethesda system and the WHO 1994 classification were used for reporting cytology and histology results. The kappa coefficient was used to determine the agreement between methods. RESULTS: the comparison between the initial cytology findings and cytology performed at the time of colposcopy revealed a kappa of 0.297 (95%CI: 0.235-0.359), indicating a fair degree of agreement. When the results of the initial cytology were compared with histopathology, a kappa of 0.261, considered to represent a fair degree of agreement, was obtained (95%CI: 0.181-0.340). A kappa of 0.408, considered to represent moderate agreement, was found when the second cytology findings were compared with the histopathology (95%CI: 0.332-0.485). CONCLUSIONS: the agreement between cytology and histology improved when cytology was repeated at the time of colposcopy, following an initial abnormal test. OBJETIVOS: avaliar se a repetição do Papanicolaou no momento da colposcopia melhora a concordância entre os métodos diagnósticos (citologia e histopatologia) do câncer do colo do útero. MÉTODOS: o estudo foi realizado no Laboratório Central de Saúde Pública do Estado de Pernambuco (LACEN/PE), de janeiro a julho de 2008, em 397 mulheres com exame citopatológico alterado encaminhadas para avaliação colposcópica. No momento da colposcopia, repetiu-se a citologia, em meio convencional. As duas citologias foram comparadas entre si e com o resultado do histopatológico obtido por biópsia dirigida pela colposcopia. A nomenclatura citológica utilizada foi Bethesda 2001 e a histopatológica a da Organização Mundial da Saúde (1994). A concordância entre os métodos foi avaliada pelo Kappa. RESULTADOS: comparando-se a citologia inicial com a citologia no momento da colposcopia, encontrou- se um Kappa de 0,297 (IC95%: 0,235-0,359), considerado fraco. Com relação à concordância citológica-histopatológica observou-se, em relação à primeira citologia, um Kappa de 0,261 (IC95%: 0,181-0,340) considerado fraco e em relação à segunda, um Kappa de 0,408 (IC95%: 0,332-0,485) este último considerado moderado. CONCLUSÕES: houve melhora da concordância citohistológica quando se repetiu a citologia no momento da colposcopia, depois de um primeiro exame alterado.